Spread of Heracleum Sosnowsky Manden in Madona District (Latvia) and Its Control Possibilities (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Heracleum sosnowsky Manden was introduced into Latvia in 1950-1960. That infancy of cultivation happened in Madona district, Barkava parish where it was cultivated from 1965 and gradually infected about 10 300 ha area of district (85% form H.sosnowsky total area in Latvia). In late eighties and early of nineties its spread in Latvia had been going out of control. H.sosnowsky Manden quickly pollutes not only open areas but also those along water reservoirs, roadsides and forest. Basic methods which were used for control of H.sosnowsky in trials were cutting, chemicals (glyphosate, dicamba, MCPA, nicosulfuron), growing of green manure plants (Italian reygrass, oil radish, buckwheat) and soil mulch with polythene.